2013
DOI: 10.1590/s0074-02762013005000002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of plasmid-mediated quinolone resistance determinants among oxyiminocephalosporin-resistant Enterobacteriaceae in Argentina

Abstract: High quinolone resistance rates were observed among oxyiminocephalosporin-resistant enterobacteria. In the present study, we searched for the prevalence of plasmid-mediated quinolone resistance (PMQR) genes within the 55 oxyiminocephalosporin-resistant enterobacteria collected in a previous survey. The main PMQR determinants were aac(6')-Ib-cr and qnrB, which had prevalence rates of 42.4% and 33.3%, respectively. The aac(6')-Ib-cr gene was more frequently found in CTX-M-15-producing isolates, while qnrB was ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…In the case of Colombia, our results are higher than reported by Karczmarczyk et al [34] in Salmonella isolated from commercial food, where 30% of the strains (n=4/13) belonging to Salmonella Infantis and Salmonella Uganda showed the presence of the qnrB gene. The high frequency of the qnrB gene in this study agrees with the previous studies in which this gene was the most commonly found in the qnr family of Enterobacteriaceae [35].…”
Section: Discussionsupporting
confidence: 92%
“…In the case of Colombia, our results are higher than reported by Karczmarczyk et al [34] in Salmonella isolated from commercial food, where 30% of the strains (n=4/13) belonging to Salmonella Infantis and Salmonella Uganda showed the presence of the qnrB gene. The high frequency of the qnrB gene in this study agrees with the previous studies in which this gene was the most commonly found in the qnr family of Enterobacteriaceae [35].…”
Section: Discussionsupporting
confidence: 92%
“…Molecular characterization of plasmid-mediated quinolone resistance (PMQR) genes in quinolone resistant asymptomatic bacteriruia isolates showed that aac(6')-Ib-cr (70%) and qepA (70%) genes were the most prevalent genes among quinolone resistant isolates in Zaria These findings agrees with the report of Cruz et al [32] who isolated aac(6')-Ib-cr and qnrB genes from enterobacteriaceae. The aac(6')-Ib-cr enzyme reduces only ciprofloxacin and norfloxacin activity by acetylation [17], the result of this study showed that all the isolates carrying the aac(6')-Ib-cr gene were resistant to Ciprofloxacin and/or Norfloxacin.…”
Section: Discussionsupporting
confidence: 87%
“…Introduction of cephalosporins antibiotic into a hospital triggers production of inducible AmpC in bacteria causing them to hyperproduce the inducible AmpC enzyme in that hospital (Thomson, 2001). β-Lactam antibiotic exposure confers resistance to the β-lactam antibiotics (Cruz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%